Subtraction ictal single-photon emission computed tomography (SPECT) co-registered to MRI (SISCOM) in presurgical diagnostics of epilepsy - E. V. Ishmuratov; A. A. Zuev (Эпилепсия и пароксизмальные состояния)
Success of surgically treated epilepsy depends on the accuracy of epileptogenic zone localization. Single-photon emission computed tomography (SPECT) using SISCOM (subtraction ictal SPECT co-registered to MRI) protocol is the only imaging method that allows identification of ictal onset zone by injection and fixation of a special radioactive tracer in the area of increased cerebral blood flow. The review outlines the key stages of SPECT using SISCOM protocol, generalizes and analyzes data for related opportunities and disadvantages as well as its prospects for use in preoperative examination of patients with epilepsy. It was demonstrated that the technique showed high sensitivity (mean 70–75%) to localize epileptogenic zone in patients with pharmacoresistant epilepsy in case if brain structural changes were not detected by magnetic resonance imaging (MRI). However, the organizational features of the procedure in combination with its specific limitations for epilepsy patients do not allow it to be considered as a routine diagnostic method.